Respuesta :

Esther

Answer:

f(-2) =-32

Step-by-step explanation:

f(x) = 5x* - 3x² + 6x + 2. f(-2)

f(-2) = 5(-2) - 3([tex]-2^{2}[/tex]) + 6(-2) + 2

f(-2) = -10 - 3(4) -12 + 2

f(-2) = -10 - 12 -12 + 2

f(-2) = (-10 - 12 -12) + 2

f(-2) = (-10 -24) + 2

f(-2) = (-34) + 2

f(-2) =-32

Hope that helps!

Answer:

[tex] \boxed{f( - 2) \: is \: - 32}[/tex]

Step-by-step explanation:

f(x) = 5x - 3x² + 6x + 2

f(-2) ?

substitute -2 as x into the equation of the function

f(-2) = 5(-2) - 3(-2)² + 6(-2) + 2

  • Note :
  • positive × negative = negative
  • (-x)² = -x × (-x)
  • negative × negative = positive

[tex]f( - 2) = - 10 - 3.4 + ( - 12) + 2[/tex]

[tex] f( - 2) = - 10 - 12 + ( - 12) + 2[/tex]

[tex] f( - 2) = - 22 - 12 + 2[/tex]

[tex]f( - 2) = - 32[/tex]